'Vaccinate my village' strategy in Malawi: an effort to boost COVID-19 vaccination. (31st December 2023) - Sethy, Ghanshyam; Chisema, Mike Nenani; Sharma, Lokesh; Singhal, Sanjay; Joshi, Krupal; Nicks, Patrick Omar; Laher, Beverly; Mamba, Kondwani Chidzammbuyo; Deokar, Kunal; Damte, Tedla; Phuka, John
ABSTRACT: Objectives: To boost COVID-19 vaccine uptake, an innovative 'vaccinate my village' (VMV) strategy using door-to-door vaccination by Health Surveillance Assistants (HSA) was adopted. In this study, we assessed the impact of the 'vaccinate my village' strategy on COVID-19 vaccine uptake. Methods: This was a cross-sectional review of the data on COVID-19 vaccination obtained from the Ministry of Health, Malawi, from 11 March 2021 to September 2022. Results: From March 2021–4 September 2022, 091, 551 COVID-19 vaccine doses were administered, out of which 2, 253, 546 were administered over just six months as a part of VMV as compared to 1, 838, 005 doses were administered over 13 months as a part of other strategies. The proportion of Malawi's population receiving at least one dose of the COVID-19 vaccine increased substantially from 4.66 to 15.4 with the implementation of the VMV strategy (p = 0.0001). District-wise coverage of the COVID-19 vaccine also increased significantly after its implementation (p = 0.0001). Conclusions: Door-to-door vaccination involving HSAs benefitted the COVID-19 vaccination program in Malawi by ensuring accessibility, availability, and acceptability.